A preliminary study of p53 oncogene expression in lung samples - Rahman, Md.Tahminur (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
This study was carried out to determine the level of expression of tumour suppressor gene p53 protein products among different types of lung lesions. The aim of this study was to determine a scientific correlation between p5 3 expression indices and different type of lung lesions. A total of 33 paraffin block lung samples of varying histological background were selected from Pathology department of three different hospitals of Malaysia. These cases comprised of benign lesions like malfonnations, emphysema, bronchiactasis, abscess, fungus and malignant lesions like different types of lung carcinomas. All the samples were submitted for routine Haematoxylin & Eosin (H&E) stains and Immunohistochemical (IH C) staining for five mutant and wild type of p53 protein products namely DO 1, BP, Phosphatase, 007 and 1801 purchased from Novocastra company, UK. The indirect IHC techniqueswere employed. The results were classified high and low level of staining using visual analogue scale suggested by Dowell and Hall. Also we counted 1 000 cells randomly from the highest area of positive staining and counted the number of cells positive for the IH C staining. The clinical symptoms found in the record sheet of these 33 patients were also analysed and correlated with the histological findings. It was found that 8(50%) of the positive samples had history of loss of appetite(LOA),Loss of weight (LOW) and cough. Haemoptysis was present in 6(37.5%), fever and other constitutional symptoms in 3 (18.75%) cases. 2 cases (12.5%) were smokers and 2(12.5%) cases were asymptomatic. The p53 expression was highest in squamous cell carcinoma (43.75%), followed by adenocarcinomas(31.25o/o )and metastatic lesions in lung ( 25o/o ). The finding of the present study is similar to other studies which showed that the p53 staining was more in squamous cell (epidermoid) carcinoma 16 of 27(59.22o/o) non small cell carcinoma 22 of 46(47.8%), small cell carcinoma 8 of 30(26.6o/o),adenocarcinomas 6 of 19(37.57o/o)2 . The result of the present study denotes the squamous malignancy as the most common phenotype for p53 positivity in lung samples and benign lesions are negative for p53 staining. However, as thesample size of this study is low the results should be interpreted cautiously and it is advocated that study with large sample size is required to substantiate these findings.